Health Practices of Turkish Expectant Mothers - Bilici, Güler; Demirezen, Esma (The European Research Journal, 2026)
Objective: Health practices during pregnancy are important to support mother - child health and the safety of the delivery. Defining these health practices can help to support vulnerable groups at risk. This study aims to determine the health practices of Turkish expectant mothers and analyze related factors.Methods: A total of 350 pregnant women were reached in this cross-sectional study from a state hospital in Istanbul during their prenatal visits. Data were collected with a Personal Information Form and Health Practices in Pregnancy Questionnaire-II (HPQ-II).Results: Most (65.1%, n=228) were between 18-31 years, mean age 29.69±6.61 (18-45) years, with junior high school degree (55.7%, n=195), and housewives (90.3%, n=316). Nearly all (98.6%, n=345) followed routine examinations, were in the second trimester (51.7%, n=181), had planned pregnancy (86.6%, n=303), but had no pregnancy school attendance (96.6%, n=338). For most expectant women (55.7%, n=195), doctors were information resources. The average HPQ-II score was 108.76±5.36 (93-123). Analysis results emphasize a significant difference between education level, smoking behavior, stillbirth, and the HPQ-II score. Especially, elementary school graduate women, smokers, and those with stillbirth experience had a lower HPQ-ll score (P